A review of Integrated Area Development (IAD) projects - Cariño, Benjamin V. (1997)
This paper examines the Integrated Area Development Approach (IAD) and its potential as a mechanism for influencing Local Government Units (LGUs) to address national concerns at local levels, and as a tool for reducing sub-national disparities in welfare through intergovernmental transfers of financial resources. A major finding of this study is that IAD strategy continues to be a valid approach for achieving the redistribution and equity objectives of the national government. However, institutional capacity-building efforts must be exerted, and more efficient intergovernmental resource transfer mechanisms must be put in place if LGUs have to assume the planning and implementation of IAD projects.
Includes bibliographical references (page 238).
Keywords: Community development; Local finance; Local government